Family Role on Schizoaffective Type Patients Treatment - Triningsih Setiawati; Khairina khairina; Syarifah Aini (Jurnal Psikiatri Surabaya, 2021)
Schizoaffective disorder is a mental disorder accompanied by schizophrenic and affective symptoms that both stand out at one time. Affective symptoms that appear are manic, depressive or both. The prevalence of patients with schizoaffective disorder is about 0.3% of the general population. Women suffer more from schizoaffective disorder and usually suffer from depressive type schizoaffective disorder. The case that will be discussed here is a young adult woman who first suffered from a schizoaffective mixed type disorder. The difficulty faced in handling this case is to provide an understanding of the patient and family about schizoaffective disorders and how patients take medication regularly for a long time. Therefore, a biopsychosocial approach is considered the most suitable to overcome the difficulties in handling this case.